PENGEMBANGAN BAHAN AJAR PRAKTIK PERBANKAN UNTUK MENINGKATKAN KOMPETENSI SISWA PADA PEMBELAJARAN AKUNTANSI DI SMK NEGERI 1 KARANGANYAR - Ambarsari, Resita Dia; Santoso, Sigit; Ivada, Elvia (Tata Arta : Jurnal Pendidikan Akuntansi, 2017)
ABSTRACTThe objective of this research is to develop practicum module learning material which is feasible and effective to be applied in the banking practicum learning at mini bank practicum room as to improve the studentsâ skill competencies in implementing the banking practicum learning. This research used the re-search and development (R&D) approach claimed by Borg and Gall. It consisted of seven phases of devel-opment, namely: (1) research and information collecting, (2) planning, (3) develop preliminary form of product, (4) preliminary field testing, (5) main product revision, (6) main field testing, and (7) operational product revision. The feasibility of the developed module was assessed through design validations by a learning media expert, a learning material expert, and an accounting practitioner, and the students with their responses. The effectiveness of the developed module use was rated through the studentsâ skill scores prior to and following the developed module use. The testing subjects included 9 students in the limited testing (small-scale), 36 in the field testing, and 21 students as the experimental subjects. Its data were col-lected through observation notes, interview, questionnaire, validation sheet, and observation sheet. They were analyzed by using the qualitative and quantitative analyses. The result of research shows that (1) the developed practicum module learning material is feasible for use as indicated by the result of validations by experts and that of feasibility testing by the students; and (2) the developed practicum module learning material is effective to be applied in the banking practicum learning so that it can improve the studentsâ skill competencies in the banking practicum learning.Keywords: Module learning material, practicum learning, skill competenciesABSTRAKTujuan penelitian ini adalah untuk mengembangkan bahan ajar Modul Praktik yang layak dan efektif untuk diterapkan pada pembelajaran praktik perbankan di ruang praktik bank mini di SMK Negeri 1 Karanganyar dalam rangka meningkatkan kompetensi keterampilan siswa dalam melaksanakan pembelajaran praktik perbankan. Penelitian ini menggunakan pendekatan penelitian dan pengembangan (R&D). Prosedur penelitian yang digunakan mengacu pada design and development research menurut Borg and Gall yang meliputi 7 tahap pengembangan yaitu: (1) research and information collection, (2) planning, (3) develop preliminary form of product, (4) preliminary field testing, (5) main product revision, (6) main field testing, dan (7) operational product revision. Kelayakan modul diukur melalui validasi de-sain oleh ahli media, ahli materi, dan praktisi akuntansi serta tanggapan dari siswa. Keefektifan penggunaan modul diukur melalui nilai keterampilan siswa sebelum dan sesudah menggunakan modul. Subjek uji coba terdiri dari 9 siswa dalam uji coba coba skala kecil dan 36 siswa dalam uji coba lapangan, serta 21 siswa sebagai subjek eksperimen. Instrumen pengumpulan data yang digunakan terdiri dari catatan observasi dan wawancara sebagai data awal serta angket, lembar validasi dan lembar observasi. Teknik an-alisis data yang digunakan adalah analisis kualitatif dan kuantitatif. Hasil penelitian menunjukkan: (1) ba-han ajar Modul Praktik yang dikembangkan dinyatakan layak digunakan menurut hasil validasi oleh ahli/pakar maupun uji coba kelayakan oleh siswa, (2) bahan ajar Modul Praktik yang dikembangkan terbukti efektif untuk diterapkan pada pembelajaran praktik perbankan sehingga mampu meningkatkan kompetensi keterampilan siswa pada pembelajaran praktik perbankan.Kata kunci: bahan ajar modul, pembelajaran praktik, kompetensi keterampilan